2021
DOI: 10.1017/pasa.2020.49
|View full text |Cite
|
Sign up to set email alerts
|

Remnant radio galaxies discovered in a multi-frequency survey

Abstract: The remnant phase of a radio galaxy begins when the jets launched from an active galactic nucleus are switched off. To study the fraction of radio galaxies in a remnant phase, we take advantage of a $8.31$ deg $^2$ subregion of the GAMA 23 field which comprises of surveys covering the frequency range 0.1–9 GHz. We present a sample of 104 radio galaxies compiled from observations conducted by the Murchison Widefield Array (216 MHz), the Australia Square Kil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 68 publications
5
28
0
Order By: Relevance
“…Brienza et al 2017;Mahatma et al 2018;Saripalli et al 2012), but these new observations probe a lower level of surface brightness than earlier studies. Another remnant radio galaxy imaged by ASKAP has also been recently reported (Quici et al 2021). However, none of the previously reported remnant radio galaxies has a circular lobe resembling that in Figure 23.…”
Section: Figure 22mentioning
confidence: 77%
“…Brienza et al 2017;Mahatma et al 2018;Saripalli et al 2012), but these new observations probe a lower level of surface brightness than earlier studies. Another remnant radio galaxy imaged by ASKAP has also been recently reported (Quici et al 2021). However, none of the previously reported remnant radio galaxies has a circular lobe resembling that in Figure 23.…”
Section: Figure 22mentioning
confidence: 77%
“…The FIRST image at 1.4 GHz and VLASS 1.2 image at 3 GHz (c,d) reveal a pair of smaller-scale (∼30 kpc) inner lobes that are roughly co-linear with the outer lobes and embedded (at least in projection) within the galaxy's optical envelope. The SDSS 9 image in (d) suggests the presence of two nuclei at the galaxy center, which are also seen in infrared images from the UKIDSS 10 Galactic Center Survey (GCS; a J-band image is shown in Figure 2 with VLASS contours overlaid). Their approximate location is marked by blue crosses in Figure 1d and their projected separation is ∼2 (∼4.4 kpc).…”
Section: Radio Imagesmentioning
confidence: 69%
“…Eventually, radiative and adiabatic expansion losses will cause the remnant emission to fade out of the observable radio band and disappear completely. The remnant phase is expected to be relatively short (a few times 10 7 years), which may explain the rarity of dying and restarted radio sources among the general population of extended radio galaxies (e.g., [5,[7][8][9][10]). However, our current knowledge of the properties, occurrence and environment of dying/restarted radio galaxies is mostly based on studies of individual objects or small collections (e.g., [4,[11][12][13][14]), and only a few investigations have been conducted using samples selected from radio surveys (e.g., [5,8,10]) or literature [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultra-steep-spectrum AGN in our sample have a wide range of radio luminosities; the median value of P 200 MHz for the AGN with α low < −1.2 (10 24.41 W Hz −1 ) is slightly lower than the median value of P 200 MHz for all AGN (10 24.61 W Hz −1 ). Quici et al (2021) show that remnant radio galaxies can be reliably identified by their ultra-steep spectra at low frequency ( 400 MHz), although the technique fails to capture younger remnants with steeper spectra at high frequencies. The absence of a radio core at high frequency is needed to establish whether these are genuine remnant radio galaxies.…”
Section: Agnmentioning
confidence: 99%